Studi Pola Persebaran Pasar Tradisional di Kota Makassar - Astarina Tambung; Arifuddin Akil; Afifah Harisah (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2016)
Along with increasing population in an area, the economic activity will also increase. Economic space can have its own character which is certainly influenced by the lifestyle of the people. One container of economic activity in urban areas is often found in the form of markets. The lifestyle of the urban community which is closely related to market preferences that has a short range (easily accessible) and practically encourages the growth of modern markets that compete with traditional markets as one of the people's economic activities in urban areas. This study aims to determine the distribution patterns of traditional markets and the factors that influence these patterns in terms of market location and consumer behavior in the city of Makassar. The research method used is a quantitative method that is supported by descriptive analysis. Analysis of patterns of distribution of traditional markets is done by grouping traditional markets based on the legality of PD Pasar Makassar Raya. There are three distribution groups, namely official permanent markets, official and informal emergencies. To find the distribution patterns of traditional markets, the nearest neighbor analysis is used. The results showed that from the calculation of the value of the T index, it was known that the distribution patterns of the official permanent traditional markets formed a random pattern, the official emergency traditional markets formed a clustered pattern and the informal markets formed a random pattern. Especially for the official permanent market, even though the T index value shows a random pattern, but by looking at the distribution map. The distribution of the official permanent market and the official official emergency predominantly cluster in the city center, while the informal market forms a pattern of spread to the center and suburbs.